2002
DOI: 10.1128/mcb.22.16.5662-5668.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Nuclear Stat1 Protein Tyrosine Phosphatase

Abstract: Upon interferon (IFN) stimulation, Stat1 becomes tyrosine phosphorylated and translocates into the nucleus, where it binds to DNA to activate transcription. The activity of Stat1 is dependent on tyrosine phosphorylation, and its inactivation in the nucleus is accomplished by a previously unknown protein tyrosine phosphatase (PTP). We have now purified a Stat1 PTP activity from HeLa cell nuclear extract and identified it as TC45, the nuclear isoform of the T-cell PTP (TC-PTP). TC45 can dephosphorylate Stat1 bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
330
2
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(343 citation statements)
references
References 37 publications
8
330
2
3
Order By: Relevance
“…However, the physiological role of these phosphatases in down-regulation of Stat5A is not clear. In fact, recent studies using TC-PTP-deficient cells have clearly demonstrated that TC-PTP is a Stat1, but not a Stat5 phosphatase (50). Although our findings provide direct evidence that Shp-2 is a Stat5A phosphatase in vivo, the possibility that there is another Stat5A phosphate(s) still exists.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…However, the physiological role of these phosphatases in down-regulation of Stat5A is not clear. In fact, recent studies using TC-PTP-deficient cells have clearly demonstrated that TC-PTP is a Stat1, but not a Stat5 phosphatase (50). Although our findings provide direct evidence that Shp-2 is a Stat5A phosphatase in vivo, the possibility that there is another Stat5A phosphate(s) still exists.…”
Section: Discussioncontrasting
confidence: 49%
“…Therefore, it is more likely that the turnover of tyrosine-phosphorylated Stat1 is mediated by a phosphatase. In fact, recent studies using cells derived from TC-PTP-deficient mice have clearly demonstrated that TC-PTP is a Stat1 phosphatase (50). In previous experiments, we demonstrated that different mechanisms are involved in regulating the inactivation of various Stat proteins (24).…”
mentioning
confidence: 99%
“…Distinct importin subtypes determine trafficking of different STATs. STAT activation with nuclear accumulation terminates within minutes [145,146]. Recently, nucleocytoplasmic shuttling of STAT3 was shown by fluorescence localization, after photobleaching (FLAP), to be a dynamic process that involves constitutive shuttling of unstimulated STAT3 in the absence of cytokine stimulation [144].…”
Section: Activation Of Stat3mentioning
confidence: 99%
“…2D), one of which localizes to the nucleus and the other to the endoplasmic reticulum (Ibarra-Sanchez et al 2000). The nuclear isoform is known to dephosphorylate several important targets in T-cells, including STAT1 (ten Hoeve et al 2002), so autoimmune disease phenotypes could certainly be influenced by the ratio of these splice forms (Todd et al 2007). CLEC2D (also known as LLT1) is a C-type lectin involved in immune response, and the PTV/T1D-associated SNP (Todd et al 2007;Wellcome Trust Case Control Consortium 2007a) is at the penultimate base of its second exon (Fig.…”
Section: Ptv In Complex Diseasesmentioning
confidence: 99%